Pengaruh Penggunaan Model Siklus Belajar (Learning Cycle) 5E Terhadap Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran IPA Kelas V SD Negeri Kota Bengkulu - Mutiara Harmaida; Endang Widi Winarni (JURIDIKDAS, 2023)
This study aims to determine the effect of using of the Learning Cycle 5E model on students critical thinking skills of class V in  SDN Bengkulu City. This type of research is quantitative, using the experimental method, with the design of The  Matching Only  Pretest-Posttest Control Group Design. Subjects in  this study were the fifth graders of SDN 51 Kota Bengkulu (control class)  and fifth grade students of SDN 60 Kota Bengkulu (experimental class) with using purposive sampling technique. The research instrument used is essay test sheet. The results of the t-gain test calculation at are thitung  equal to 4,16 bigger than equal to ttabel 2,01 which means that there is a significant influence on the use of the  Learning  Cycle  5E  model  on  students'  critical  thinking  skills.  The conclusion in this study is that there is an effect of the use of the 5E Learning Cycle model on Students' Critical Thinking Ability of class V Natural Sciences in SDN kota Bengkulu.